Canning Basin - Petroleum Systems Analysis. Issue 1 (1st December 2018) - Murray, Andrew; Edwards, Casey; Long, David
Abstract : New high resolution geochemical information was acquired for fluids from recent Canning Basin wells and interpreted in context with previous work on fluid typing and correlation by Geoscience Australia (GA). Ungani field oils are interpreted to be derived from the same/very similar clastic source rock, comprising bacterial and marine algal matter deposited under anoxic to sub-oxic conditions, and generated within the peak oil window for a high quality marine source rock. Observed low GOR's are the consequence of both source rock type and gas removal. Liquids from the Yulleroo field are derived from a similar source to the Ungani oils, with the addition of dry gas from a higher maturity and/or more gas prone source, and generated and expelled at slightly higher maturity. The current lean gas condensate phase is the result of the addition of dry gas combined with minimal water washing. In nearly all aspects the Ungani and Yulleroo liquids resemble the L4 family previously attributed by GA to a probable Carboniferous age source. Gas-condensate from the Valhalla North-1 field was derived from a more mature source rock deposited in an oxic environment and containing more gas prone (terrigenous) organic matter. Map based modelling incorporated eleven 1D models in the Ungani-Yulleroo and Valhalla-Asgard region, and a map based burial history and maturity model. The source rock model was derived from the liquid geochemistry results rather than the poor quality source rock potential data gathered to date. Burial history modelling and maturity modelling at the top of the Lower Laurel Carbonate shows maturity for gas expulsion in the main trough and oil to light oil expulsion on the flanks of the basin. Maximum burial in the basin took place immediately prior to the Fitzroy Uplift, resulting in the main phase of oil generation and expulsion taking place around 200Ma.